2001
DOI: 10.1046/j.1525-1438.2001.01019.x
|View full text |Cite
|
Sign up to set email alerts
|

Early development of vaginal shortening during radiation therapy for endometrial or cervical cancer

Abstract: Vaginal necrosis can occur following radiation therapy for gynecological malignancies. The distal vaginal mucosa has a poorer radiation tolerance than the mucosa in the upper region. We examined the extent of vaginal shortening in patients treated by intravaginal brachytherapy with or without pelvic irradiation. Maximal extension of the vaginal cylinder above the pubis was measured for each insertion. We found that the difference in mean values between insertions (2.3 vs. 1.7 cm) was highly statistically signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 6 publications
3
23
0
4
Order By: Relevance
“…A significant difference in vaginal length occurred between the first and second treatment for patients treated with external beam and brachytherapy but not with brachytherapy alone. 26 Our results revealed similarly reported outcomes between the 2 groups in all areas of QOL, including sexual functioning. However, both groups report sexual and vaginal changes; and many patients in both groups were not sexually active.…”
Section: Discussionsupporting
confidence: 83%
“…A significant difference in vaginal length occurred between the first and second treatment for patients treated with external beam and brachytherapy but not with brachytherapy alone. 26 Our results revealed similarly reported outcomes between the 2 groups in all areas of QOL, including sexual functioning. However, both groups report sexual and vaginal changes; and many patients in both groups were not sexually active.…”
Section: Discussionsupporting
confidence: 83%
“…The decrease in vaginal length may explain in part the increased dyspareunia. Vaginal shortening can occur during the course of intracavity and external irradiation (27)(28)(29). In the present study the vaginal length was smaller in patients submitted to CT/RT or RT when compared to the RH group.…”
Section: Discussionsupporting
confidence: 46%
“…The PORTEC-2 trial showed that only 15% of the patients were sexually active after surgery, this increased significantly to 39% during the first year and sexual functioning and symptoms did not differ between vaginal BRT and EBRT at a median follow up of 2 years 15. Several large studies have shown that a large proportion of patients with endometrial cancer have sexual dysfunctions after vaginal BRT 16,17. However, in a prospective study by Quick et al, vaginal BRT patients had sexual functions similar to women treated with surgery alone 15,18.…”
mentioning
confidence: 99%